Effect of amorphous complexions on plastic deformation of nanolayered composites. (1st July 2023) - Yan, Zhe; Liu, Zhaorui; Yao, Bonan; An, Qi; Zhang, Ruifeng; Zheng, Shijian
Abstract: Interface-induced dislocation nucleation and interface sliding are two decisive mechanisms to understand plastic deformation of nanolayered composites. Taking the Cu-Nb system as a prototype, with atomic simulations, we reveal the atomic mechanism of dislocation nucleation and interface sliding after introducing the CuNb amorphous complexions with different compositions. Under tension loading, the initial nucleation sites correspond to the localized shearing region, and the amorphous composition can regulate the ordering degree of crystalline/amorphous interfaces. Under shear loading, the pathway of interface sliding corresponds to the low-energy region of the energetic landscape, and the shear resistance increases with the increase of Cu content owing to the enhancement of the sliding barrier. These findings reveal the influence of the amorphous complexions on plastic deformation, and provide theoretical guidance for the design of nanolayered composites. Graphical abstract: Image, graphical abstract